Effects of p,p'-dichloro diphenyl trichloroethane (DDT) on the morphometry and ultrastructure of the protoconch of the oyster drill Urossalpinx cinerea (say) (prosobranchia: muricidae) - Fernández, Gustavo E. ([editor no identificado], 1984)
Tesis (Master of Science in Marine Studies)--University of Delaware, 1984.